Changing times for science and the public: Science journalists’ roles for the responsible communication of science - Liskauskas, Suzana (EMBO Rep, 2019)
The increasing number of corrections in the scientific record and the debate about reproducibility affect journalists’ reporting about science and thereby public opinion on scientists and research.[Image: see text]